SEROPREVALENCIA DE Neospora caninum EN LLAMAS DE LA PROVINCIA DE MELGAR, PUNO - Moya F., Raúl (2003)
Neosporosis, caused by the protozoan Neospora caninum, has been associated with reproductive problems in cattle worldwide, and has been found in a variety of animal species, including camels. The aim of this work was to determine the seroprevalence of Neospora caninum in two llama herds of Melgar province, Puno. Two hundred seventy five serum samples of female llamas from the districts of Santa Rosa and Nuñoa were tested using the indirect inmunofluorescense test (IFAT) to detect antibodies against N. caninum. The 16.7 ± 4.4% (46/275) of the serum samples had antibodies at 1:50 dilution, indicating a moderate seroprevalence in the herds. The seroprevalence in Santa Rosa was lower (4.6 ± 4.4%, 4/86) than in Nuñoa (22.2 ± 5.9%, 42/189), and with statistical differences between herds (p<0.05). No differences due to age were found (p>0.05). This study confirms the presence of Neospora caninum in female llamas from Melgar province, Puno.